A Declamation on a Sopatrian Model: P.Hamb. II 134 Reconsidered. Issue 1 (1st January 2020) - Kanavou, Nikoletta; Papathomas, Amphilochios
Abstract : In this paper, we revisit P.Hamb. II 134, which preserves a fragmentary declamation on the familiar aristeus theme, suggest a number of improvements to the text and provide an English translation. We further argue that the speaker in our piece is an aristeus, probably a father, who addresses his son, a deserter, in opposition to recent interpretations that reckon the speaker to be a deserter–father and the addressee to be his aristeus –son. Our interpretation evokes a scenario that is found in Sopater 5.44.27–45.10 Walz. Based on the fragment's content and style, we suggest that either Sopater or his contemporary Libanius could be the author of the lost declamation partially transmitted by this fragment.